2010
DOI: 10.1007/s11746-010-1560-7
|View full text |Cite
|
Sign up to set email alerts
|

Entrapment of Flaxseed Oil Within Gelatin‐Gum Arabic Capsules

Abstract: The aim of this study was to optimize the encapsulation of flaxseed oil within a gelatin-gum Arabic (GA) matrix via complex coacervation. The effect of homogenization rates (3,000-15,000 rpm) and total biopolymer concentrations (1-2% w/v) on emulsion efficiency was studied in order to optimize the wall matrix. The physicochemical properties of the dried powder, and the capsule's ability to inhibit oxidation during storage were assessed. As homogenization rates increased from 3,000 to 9,000 rpm, the structure o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
52
1
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 130 publications
(58 citation statements)
references
References 22 publications
3
52
1
2
Order By: Relevance
“…The content of surface oil (content of non-encapsulated oil in pumpkin seed oil powder) was determined by the washing method described by Liu et al (2010) with modification. Hexane (50 mL) was added to 5 g of powder in a 250-mL flask, and the sample was shaken for 5 min.…”
Section: Basic Parameters Of Pumpkin Seed Oil Powdersmentioning
confidence: 99%
See 2 more Smart Citations
“…The content of surface oil (content of non-encapsulated oil in pumpkin seed oil powder) was determined by the washing method described by Liu et al (2010) with modification. Hexane (50 mL) was added to 5 g of powder in a 250-mL flask, and the sample was shaken for 5 min.…”
Section: Basic Parameters Of Pumpkin Seed Oil Powdersmentioning
confidence: 99%
“…Multinuclear capsules are generally considered as having better controlled release properties than mononuclear ones. The first type of capsules are capable of releasing their contents slowly over time upon complete or partial degradation of the matrix, whereas the second type release their contests instantly (Liu et al 2010). Table 3 presents results of fatty acid composition determination.…”
Section: Color Size and Morphology Of Pumpkin Seed Oil Powdersmentioning
confidence: 99%
See 1 more Smart Citation
“…Peroxides can degrade further into secondary oxidative products such as aldehydes and ketones to give additional loss to product sensory quality (Liu et al 2010). Reaction between aldehydes and thiobarbituric acid is the base of measuring TBA value (Pokorny and Dieffenbacher 1989).…”
Section: Oxidative Stabilitymentioning
confidence: 99%
“…These results can be due to the role of coating material since Arabic gum and hydrogenated fat can form a film around ground flaxseed and keep it safe from oxygen attack. Liu et al (2010) reported that encapsulation of flaxseed oil with gelatin-Arabic gum matrix decrease oxidation in flaxseed oil.…”
Section: Oxidative Stabilitymentioning
confidence: 99%